The Political Economy and Metal Trade in Bronze Age Europe: Understanding Regional Variability in Terms of Comparative Advantages and Articulations - Earle, T; J., Ling; C., Uhnér; Z., Stos-Gale; L., Melheim (European Journal of Archaeology, 2015)
In the second millennium cal BC, a new metal conquered Europe: the alloy of copper and tin that improved the quality of tools and weapons. This development, we argue, initiated a framework for a new political economy. We explore how a political economy approach may help understand the European Bronze Age by focussing on regional comparative advantages in long-distance trade and resulting bottlenecks in commodity flows. Links existed in commodity chains, where obligated labour and ownership of resources helped mobilize surpluses, thus creating potential for social segments to control the production and flows of critical goods. The political economy of Bronze Age Europe would thus represent a transformation in how would-be leaders mobilized resources to support their political ends. The long-distance trade in metals and other commodities created a shift from local group ownership towards increasingly individual strategies to obtain wealth from macro-regional trade. We construct our argument to make sense of available data, but recognize that our model's primary purpose is to structure future research to test the model.
Articolo in fotocopia
Keywords: Europa, Età del Bronzo, economia politica, commercio metalli, variabilità regionale